Current Status of First-Grade Students’ Adaptability in Learning Activities - Lam, Phan Quoc; Thanh, Duong Thi Thanh; Hoa, Ho Quang (Journal of Ecohumanism, 2024)
This study surveys the current state of adaptability in learning activities among first-grade students, aiming to assess their capacity to adjust as they transition from preschool to primary school. The research identifies the challenges and advantages students encounter in learning activities and explores factors affecting their adaptability. An objective assessment scale was developed to measure the formation of adaptability in first-grade students, surveying 168 students. Additionally, a teacher-assessment scale was created to evaluate teacher observations of first-grade students’ adaptive behavior in learning activities, covering 117 teachers and 23 classes across two provinces, Nghe An and Ha Tinh. All pairs of variables compared showed relatively strong positive correlations (ranging from a minimum of 0.38 to a maximum of 0.66). Consequently, it can be observed that the adaptability level of first-grade students in learning activities is closely related to their academic outcomes. The correlation coefficient between academic outcomes and behavior in low-determined situations was 0.65, which is higher than in high-determined situations (0.53). Therefore, the adaptability of first-grade students in learning activities is closely associated with their academic performance. Results from 117 surveyed teachers with first-grade teaching experience indicate that 100% agree that adaptability significantly influences students’ learning processes and outcomes; 98.29% believe it is essential to focus on improving student adaptability in first-grade instruction.